Effectiveness Of eHealth Application In Community Nursing Settings: Literature Review - Kinantika Nur Dewanti; Sukihananto Sukihananto (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2021)
Introduction: Health promotion usually done by health professional as a community nursing to target group. However, the awareness about the importance of health promotion in society was lacked. Society that joined health promotion usually group that had an illness. This condition has caused the lack of knowledge, access, and community interest in this activity. The solution that can be done by health professional especially community nursing is develop a method by current technology. The technology is called electronic health (eHealth). Objective: to determine the effectiveness of eHealth application in community nursing setting Methods: this study uses a literature review from UI's online database about electronic health (e-health). The article search process are accessed through internet data base searches, namely ProQuest, Science Direct, PubMed, Ovid, Wiley Online Library and Sage. Based on the review journal found 10 journals that have correlation with electronic health (eHealth). The results of the literature review were start from 2015-2020. Results: the results of the literature show that eHealth was current technology than can increase the health service and health status. Conclusion: Electronic Health (eHealth) is a solution for health service which suitable with current technology and can be applied in community nursing setting.